A new genus and species of axiid shrimp (Crustacea, Decapoda) from a southwestern Indian Ocean seamount - Dworschak, Peter C. (European Journal of Taxonomy, 2016)
A new genus and species of axiid shrimp, Montanaxius mediumquod gen. et sp. nov., is described and illustrated based on three specimens collected from hexactinellid sponges from a seamount in the southwest Indian Ocean. The new genus is characterized by a laterally denticulate rostrum, short lateral carina, absence of submedian carina, a prominent toothed median carina, round pleomere pleura 2–5, pleurobranchs on second to fourth pereopods, and the presence of a male first pleopod and appendix interna on pleopods 3–5. It most closely resembles Levantocaris Galil & Clark, 1993 and Planaxius Komai & Tachikawa, 2008, but differs from the former by being gonochoristic, having a strongly elevated gastric region and well-developed eyes, and from the latter by its toothed median carina and the presence of a median telson spine.